Teaching English at Junior High School in Indonesian Rural Area : The Implementation of Scientific Approach - Christi Agustin Malaikosa; Lita Liviani Taopan (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2020)
The creation of the curriculum aims to improve the quality of education in the country. It is also happening in Indonesia, where the curriculum is always created with the aim of improving the quality of education in Indonesia. The aim of this study was to investigate the implementation of a scientific approach to teaching English in Junior High School in the Indonesian rural areas context. Qualitative method used in this study on pilot project school of 2013 curriculum. The research subject was the English language teacher who has been teaching using the 2013 curriculum. The data then analyzed using Analysis Interactive's Miles, Huberman, and Saldana model. It can be found that the teacher already implements the scientific steps consist of (observing, questioning, collecting data, associating, and communicating). On the other hand, there was still a lot of problem face by the teacher while applying this method, such as a lot of time is spent on this activity, a large number of students, limited time allocation given and also lack of teaching source.Keywords: English Teaching, Implementation, Scientific, Rural Area